Changes in Sensory Phenomena, Tics, Obsessive–Compulsive Symptoms, and Global Functioning of Tourette Syndrome: A Follow-Up After Four Years - Kano, Yukiko; Fujio, Miyuki; Kaji, Namiko; Matsuda, Natsumi; Nonaka, Maiko; Kono, Toshiaki (Frontiers in Psychiatry, 2020)
Sensory phenomena and related features of Tourette syndrome are related to poorer quality of life. Therefore, sensory phenomena might also have a negative impact on global functioning. However, the influence of sensory phenomena, tics, and obsessive-compulsive symptoms (OCS) on global functioning after several years of usual treatment has not been investigated. Twenty out of 45 Japanese patients with Tourette syndrome who had previously undergone an evaluation of these clinical features were assessed again after an average of four years. We conducted a panel of assessments for premonitory urges, broader sensory phenomena, tic severity, OCS, and global functioning. Based on Pearson’s correlation coefficient, current global functioning was significantly negatively correlated with previous tics and marginally negatively correlated with previous broader sensory phenomena. Current global functioning was marginally correlated with change in tics. Change in global functioning was significantly correlated with change in OCS and marginally correlated with change in premonitory urges. Due to the small sample size, it was not possible to use a multiple regression analysis to conclude that sensory phenomena, tics, and OCS predict global functioning in adolescents and adults with TS. However, it was suggested that further investigation of this relationship would be meaningful.